WAKAF PRODUKTIF DALAM PERSPEKTIF MAQASID SYARIAH - Arif Zunaidi (Al'Adalah, 2022)
Giving has become a habit in our culture. Unfortunately, in our society's view, waqf tends to focus on land and buildings. The meaning of a waqf event can be interpreted more broadly; it can be managed to be more productive, for example. This study uses library research methods that show productive waqf from the perspective of maqasid sharia, including ijtihad maslahi, which must be based on the main objectives of religion. Second, ijtihad maslahi must be based on knowledge of maslahah al-shar'iah (maslahat in religion). Third, ijtihad maslahi must apply and consider the public benefit of understanding the text in both al-Qur'an and Hadith. Fourth, ijtihad maslahi must consider the point of view of profit and loss.